Phenotypic Evaluation and Genetic Analysis of Seedling Emergence in a Global Collection of Wheat Genotypes (Triticum aestivum L.) Under Limited Water Availability - Francki, Michael G.; Stainer, Grantley S.; Walker, Esther; Rebetzke, Gregory J.; Stefanova, Katia T.; French, Robert J. (Frontiers in Plant Science, 2021)
The challenge in establishing an early-sown wheat crop in southern Australia is the need for consistently high seedling emergence when sowing deep in subsoil moisture (>10 cm) or into dry top-soil (4 cm). However, the latter is strongly reliant on a minimum soil water availability to ensure successful seedling emergence. The aims of this study were to (1) evaluate 233 Australian and selected international wheat genotypes for consistently high seedling emergence under limited soil water availability when sown in 4 cm of top-soil in field and glasshouse studies; (2) ascertain genetic loci associated with phenotypic variation using a genome-wide association study (GWAS); (3) compare across loci for traits controlling coleoptile characteristics, germination, dormancy and pre-harvest sprouting. Despite significant (P<0.001) environment and genotype-by-environment interactions within and between field and glasshouse experiments, eight genotypes including five cultivars, two landraces, and one inbred line had consistently high seedling emergence (mean value >85%) across nine environments. Moreover, 21 environment-specific QTL were detected in GWAS analysis on chromosomes 1B, 1D, 2B, 3A, 3B, 4A, 4B, 5B, 5D and 7D, indicating complex genetic inheritance controlling seedling emergence. We aligned QTL for known traits and individual genes onto the reference genome of wheat and identified 16 QTL for seedling emergence in linkage disequilibrium with coleoptile length, width and cross-sectional area, pre-harvest sprouting and dormancy, germination, seed longevity and anthocyanin development. Therefore, it appears that seedling emergence is controlled by multifaceted networks of interrelated genes and traits regulated by different environmental cues.